Influence of outdoor air pollution on cardiovascular diseases in Madeira (Portugal) - Camacho, Irene (2021)
Previous studies suggest that human exposure to atmospheric pollution can trigger cardiovascular diseases (CVDs). This study aimed at assessing the influence of short-term exposure to atmospheric pollution in the occurrence of CVD and mortality in Madeira. A single-centre retrospective study was conducted during 2005–2011. Air pollutant data and meteorological parameters were gathered. Daily admissions at the emergency service due to CVD and markers levels for cardiac function were obtained from a public hospital. Exploratory and correlation analysis of all variables were performed, and the CVD relative risk (RR) of hospital admissions and mortality was calculated. During the study, mean annual concentrations of the air pollutants varied greatly, with NOx and O3 showing the highest annual average concentrations. Two hundred ten thousand five hundred forty patients were admitted at the emergency service, 74% of them due to cardiovascular causes. Hospital admissions were positively correlated with PM2.5, and SO2. A positive and significant association between PM2.5 with creatine kinase myocardial band and B-type natriuretic peptides markers was found, whilst SO2 was positively associated with Creatine kinase myocardial band. The RR seemed to increased with PM2.5 and NOx exposure. Traffic-related pollutants were weakly but statistically associated to hospital admissions due to CVD and mortality. PM2.5 and SO2 were related with higher hospital admissions which in turn seemed to increase the serum markers. The risk of mortality was mainly associated with O3 and average air temperature. Adults and elders seem to be more susceptible to atmospheric pollutants, particularly in the winter.